Current status of nephroprotection in diabetology Aktueller Stand der Nephroprotektion in der Diabetologie - Schmieder, Roland; Striepe, Kristina (Die Diabetologie, 2024)
Type 2 diabetes (T2DM) is the most common cause of chronic kidney disease (CKD), with about 40% of patients with T2DM developing CKD. The possibilities for nephroprotection have significantly expanded recently. In addition to the well-known nephroprotective effects of renin–angiotensin system inhibitors, there are additional evidence-based treatment options to reduce the progression of CKD, and possibly prevent it in some cases. In addition to antihypertensive, antihyperglycemic and lipid-lowering therapies, sodium–glucose cotransporter 2 (SGLT2) inhibitors, glucagon-like peptide‑1 (GLP-1) receptor agonists and nonsteroidal mineralocorticoid receptor antagonists are now well established in national and international guidelines for treating CKD in T2DM. Holistic, individualized, and early treatment is important for patients with T2DM and CKD.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Diabetes mellitus; type 2; Diabetic nephropathies; Guideline; Kidney protection; Mineralocorticoid receptor antagonists